AaCycTL Regulates Cuticle and Trichome Development in Arabidopsis and Artemisia annua L. - Dong, Boran; Wang, Xingxing; Jiang, Rui; Fang, Shiyuan; Li, Jinxing; Li, Qing; Lv, Zong you; Chen, Wan sheng (Frontiers in Plant Science, 2021)
Artemisinin is an important drug for resistance against malaria. Artemisinin is derived from the glandular trichome of leaves, stems or buds of the Chinese traditional herb Artemisia annua. Increasing the trichome density may enhance the artemisinin content of A. annua. It has been proven that cyclins are involved in the development of trichomes in tomato, Arabidopsis and tobacco, but it is unclear whether the cyclins in A. annua influence trichome development. In this study, we showed that AaCycTL may regulate trichome development and affect the content of artemisinin. We cloned AaCycTL and found that it has the same expression files as the artemisinin biosynthesis pathway gene. We overexpressed AaCycTL in Arabidopsis, and the results indicated that AaCycTL changed the wax coverage on the surface of Arabidopsis leaves. The trichome density decreased as well. Using yeast two-hybrid and BiFC assays, we show that AaCycTL can interact with AaTAR1. Moreover, we overexpressed AaCycTL in A.annua and found that the expression of AaCycTL was increased to 82-195%. Changes in wax coverage on the surface of transgenic A. annua leaves or stems were found as well. We identified the expression of the artemisinin biosynthesis pathway genes ADS, CYP71AV1 and ALDH1 has decreased to 88-98%, 76-97% and 82-97% in the AaCycTL-overexpressing A. annua lines, respectively. Furthermore, we found reduced the content of artemisinin. In agreement, overexpression of AaCycTL in A. annua or Arabidopsis may alter waxy loading, change the initiation of trichomes and downregulate trichome density. Altogether, AaCycTL mediates trichome development in A. annua and thus may serve to regulate trichome density and be used for artemisinin biosynthesis.